Instructional Leadership Styles on Students’ Academic Performance in Public Secondary Schools in Tarime Urban District, Mara-Tanzania - Musumi, Kaitira; Mkulu, Demetria Gerold (International Journal of Humanities and Education Development (IJHED), 2020)
This study explores the instructional leadership styles on students' academic performance in public secondary schools in Tarime Urban District, Mara-Tanzania. The study identifies the contribution of instructional leadership styles on students' academic performance, find out the challenges encountered by heads of school on the practice of instructional leadership styles towards students' academic performance and to establish measures to be taken to enhance the instructional leadership styles to promote students' academic performance. The study adopted a mixed research approach and a convergent parallel design where qualitative and quantitative were used in a single study. The questionnaires and interview guide tools were used to collect data. A sample size of 90 respondents out of 151 populations was used. Qualitative data were categorized to get themes while quantitative data was analyzed using descriptive with the aid of Statistical Package for Social Science (SPSS) version 21. Instruments such as questionnaires were validated and reliability was checked and gives the correlation coefficient of 0.725 indicating that the instruments were valid and reliable to go to the field for data collection. Data were analyzed using descriptive and inferential statistics and the findings indicated that the use of instructional leadership style by well-defining school vision and goal to teachers, providing adequate instructional resources, supervising and monitoring them effectively can improve their job performance which enhances student academic performance. However, this study unveiled that instructional leadership style is hindered by several challenges including shortage of funds, poor school infrastructures, shortage of teaching and learning resources and students and teachers truancy. The study concluded that the government should provide in-service training to school heads to improve their leadership skills especially on instructional leadership style, also ensure a conducive working environment including infrastructures and teaching and learning materials.